GE_GERICHTE P/12554/2010 vom 10. Dezember 2014 - GE Cour de justice (2014)
IN DUBIO PRO REO; TENTATIVE(DROIT PÉNAL); VIOL; CONTRAINTE(DROIT PÉNAL); MENACE(DROIT PÉNAL); FIXATION DE LA PEINE | CP.42; CP.43; CP.47; CPP.433